Mapping Network Activity in Sleep - Shiromani, Priyattam J.; Blanco-Centurion, Carlos; Vidal-Ortiz, Aurelio (Frontiers in Neuroscience, 2021)
It was in the influenza pandemic of 1918 that von Economo identified specific brain regions regulating sleep and wake. Since then researchers have used a variety of tools to determine how the brain shifts between states of consciousness. In every enterprise, new tools have validated existing data, corrected errors, and made new discoveries to advance science. The brain is a challenge, but new tools can disentangle the brain network. We summarize the newest tool, a miniature microscope, that provides an unprecedented view of the activity of glia and neurons in freely behaving mice. With this tool, we have observed that the activity of a majority of GABA and MCH neurons in the lateral hypothalamus is heavily biased towards sleep. We suggest that miniscope data identifies activity at the cellular level in normal versus diseased brains, and also in response to specific hypnotics. Shifts in activity in small networks across the brain will help identify the point of criticality that switches the brain from wake to sleep.